Hypoxia-Induced Downregulation of miR-29 in Renal Tumor Cells Affects Collagen IV Subunit Expression through Multiple Sites - Chuncheng Liu; Linan Liu; Jinlai Bo; Xian Lu; Donghui Qu; Gehui Liu; Zhiyan Jiang; Lu Cai (Biomedicines, 2022)
Multiple tumor exacerbations and treatment procedures, such as extracellular matrix remodeling, metabolic reprogramming, immunological evasion, and resistance to chemotherapy and radiotherapy, are influenced by intratumoral hypoxia. It is becoming increasingly clear how hypoxia interacts with the extracellular matrix and how this affects the growth of cancer. We analyzed the published sequencing results of hypoxia-stressed mouse kidney tumor cells and found that the expression of miR-29b was significantly downregulated. There are several sites that are complementary to the miR-29 seed sequence in the 3’ non-coding regions (3’UTRs) of various extracellular matrix-related genes, including collagen IV. We analyzed the sequences of the 3’UTRs of different subunits of collagen IV in different species and constructed the corresponding phylogenetic trees. We found that the 3’UTRs of Col4a1 and Col4a4 may have been subjected to particular evolutionary pressures. By cloning the 3’UTRs of collagen IV subunits into the psiCHECKTM-2 vector, we found that seven of the eight sites in the Col4a3–Col4a6 gene complementary to miR-29 were significantly repressed by miR-29a, b (except for the 7774–7781 of Col4a3 gene). The inhibitory efficiency of miR-29a, b on these seven sites was between 27% and 57%. The research on the regulation of miR-29 and extracellular matrix by hypoxia can provide a theoretical basis for tumor and fibrosis research and treatment.